The role of fintech in mitigating information friction in supply chain finance - Hsiao-Hui Lee; S. Alex Yang; Kijin Kim (Asian Development Bank (ADB), 2019)
Micro, small, and medium-sized enterprises in developing countries face severe financing difficulties, especially when trying to expand internationally. "Information friction" is a significant cause of this financing gap. Recent financial technologies (fintech) can improve supply chain finance efficiency. This paper therefore proposes a conceptual and analytical framework to study how fintech can close the financing gap by reducing information friction. We classify fintech into two categories: information processing technology (Type-A) and information collecting technology (Type-B) and find that both help close the financing gap by lowering the probability of misclassification of good firms as bad. Banks' optimal Type-A investment increases in the bank's size, profit margin, and the fraction of good firms in the market. They invest in Type-B if and only if the investment is sufficiently small. Due to "double marginalization," a bank's optimal fintech investment is lower than a socially optimal level, calling for mechanisms to incentivize or complement banks' investment in fintech.
Keywords: O14; O24; O31; 330; artificial intelligence; digitization; fintech; information friction; supply chain finance